2021
DOI: 10.1111/acps.13387
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of psychotherapy and cognitive remediation to target cognition in mood disorders

Abstract: Objective To examine the impact of a treatment package combining Interpersonal and Social Rhythm Therapy (IPSRT) and cognitive remediation (CR), vs IPSRT alone, on cognition, functioning, and mood disturbance outcomes in mood disorders. Methods A pragmatic randomised controlled trial in adults with bipolar disorder (BD) or major depressive disorder (MDD), recently discharged from mental health services in Christchurch, New Zealand, with subjective cognitive difficulties. Individuals were randomised to a 12‐mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…poor cognition at baseline was associated with better CR response) out of a total of 16 candidate predictors (cognitive, functional, demographic, clinical) 5 . In contrast, data from the RCTs by Ott et al and Douglas et al showed no associations between baseline objective (executive function 1 and global cognition 3 ) and subjective cognition and CR‐associated improvement in cognition. Douglas et al, in as‐yet unpublished analyses, have reported predictive effects of demographic and clinical variables on CR‐related cognitive effects.…”
Section: Predictors Of Response To Cognitive Remediationmentioning
confidence: 92%
See 2 more Smart Citations
“…poor cognition at baseline was associated with better CR response) out of a total of 16 candidate predictors (cognitive, functional, demographic, clinical) 5 . In contrast, data from the RCTs by Ott et al and Douglas et al showed no associations between baseline objective (executive function 1 and global cognition 3 ) and subjective cognition and CR‐associated improvement in cognition. Douglas et al, in as‐yet unpublished analyses, have reported predictive effects of demographic and clinical variables on CR‐related cognitive effects.…”
Section: Predictors Of Response To Cognitive Remediationmentioning
confidence: 92%
“…First, similar samples in terms of diagnoses and inclusion criteria across studies are needed to be able to pool data for larger-scale prediction analyses. Regarding the impact of the diagnosis on CR response, whilst Strawbridge et al 2 did not observe a difference in CR response between BD type I and II, Douglas et al 3 reported that their BD sample showed larger pro-cognitive effects than MDD. Thus, pooling data in MDD and BD samples separately may identify predictors specific to each group.…”
Section: Me Thodolog Ic Al Consider Ations and Recommendationsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the former, the removal of Ott et al (2021b) or Tsapekos et al (2023) rendered the observed effects nonsignificant, and similarly did the removal of either of two studies (Gomes et al, 2019;Lewandowski et al, 2017) in the latter variable. Interestingly, the removal of Douglas et al (2022), which is the only study including patients with different mood states and exploring a combination of psychological treatments, did not change the overall effects. Similarly, the exclusion of Torrent et al (2013) /Bonnin et al (2016b), which used a different CR approach, did not change the overall outcome.…”
Section: Sensitivity Analysismentioning
confidence: 94%
“…Only three RCTs considered cognitive impairment subjectively (Demant et al, 2015;Douglas et al, 2022) or objectively measured (Ott et al, 2021a(Ott et al, , 2021b as an inclusion criterion, whereas the RCT by Torrent et al (2013) considered the presence of moderate-to-severe functional impairment defined as a score ⩾ 18 on the Functioning Assessment Short Test (FAST) (Rosa et al, 2007) together with a score ⩾ 4 in the cognitive domain of the same scale for inclusion in the study.…”
Section: Clinical Characteristics Of the Samplesmentioning
confidence: 99%